(untitled) (Kronika Bydgoska, 2013)
On January 19, 1947, the first post-war Legislative Seym election was held in Poland. Bydgoszcz, the capital of Pomerania Voivodeship, became the region’s most important place of the electoral campaign held at that time. Due to the presence of the state administration representatives and the voivodeship party authorities, the biggest propaganda events took place in the city on the Brda River. Due to the same reasons, the communists’ priority was the right ”protection” of the city from anticipated forms of the society’s resistance - special patrols were established for this purpose, and in workplaces additional ”protection” was assigned. At the same time, in Bydgoszcz the same abuse was committed as in other regions of the voivodeship and Poland - electoral boards were assembled only from representatives of the Polish Workers’ Party (PPR) and so-called allied parties, and opponents of the communist dictatorship were deprived of the right to vote or arrested. On the election day, violation of the principle of secret voting and other electoral regulations was prevalent.